Efeito do exercício prévio severo no modelo de potência crítica de dois e três parâmetros - Nakamura, Fábio Yuzo; Okuno, Nilo Massaru; Rosa, Camila Ferreira Infante; Cyrino, Edilson Serpeloni; Simões, Herbert Gustavo; de-Oliveira, Fernando Roberto; Cardoso, Jefferson Rosa; Kokubun, Eduardo [UNESP] (My University, 2007)
The purpose of this study was to apply the two and three-parameter critical power model equations after depletion of a fixed amount of anaerobic work capacity (AWC), followed by a short rest period. Sixteen subjects underwent: (1) two practice trials for ergometer familiarization to severe exercise; (2) 4-5 exercise bouts on different days for the estimation of critical power (CP) and AWC using the two and three parameter models; (3) the same procedures as described in stage 2 were repeated after 30 s recovery from 180 s of exercise completed at an intensity that would have elicited exhaustion in around 300 s. The CP2parameter (130-174 W versus 131-170 W) and CP3parameter (108 versus 100 W) estimated after prior severe exercise followed by a short rest period remained stable compared to the fatigue-free tests. The AWC2parameter was reduced in response to prior severe exercise. The AWC3parameter was not significantly reduced. The correlations between CP2parameter derived from the same equation with and without prior AWC2parameter reduction were strong (r = 0.97-0.99, P < 0.001). The correlation was merely moderate (r = 0.62, P = 0.01) when CP3parameter was analyzed. It can be concluded that the two-parameter critical power model provides a coherent mathematical description of the reduced mechanical output induced by a prior fatiguing task, since AWC2parameter was affected while CP2parameter estimates remained constant.
Effects of previous severe exercise on two and three parameter critical power modeling
Keywords: Anaerobic work capacity; Critical power; Prior exercise